Development of a microfluidic flow cytometry platform with fluorescence and light scattering detection for the rapid characterization of circulating tumor cells - Stewart-James, Samantha Ann (Kansas State University, 2015)
Circulating tumor cells (CTCs) have become a key component in the identification and treatment of cancer. Once dislodged from the main tumor, CTCs travel through the bloodstream and cause metastasis. Early detection and identification of these cells can help in the evaluation and prognosis of various types of cancer, as well as assisting in patient treatments by determining the spread of the disease. Here, a high-throughput microfluidic analysis technique is described that can efficiently detect and identify cells, with the specific identification of CTCs as a future application through fluorescent labeling in mind. As proof of principle, the device has been shown to detect and characterize individual human Jurkat (T-lymphocyte) cells at a rate of 100 cells/minute. The device employs micro-scale flow focusing to isolate individual cells. The cells are detected using both light scattering and laser-induced fluorescence to evaluate cell size and surface functionality.
Keywords: Microfluidics; Flow cytometry; Single rare cell; Circulating tumor cell; Method development; Single-point detection; Chemistry (0485)